Credit default swap spreads and systemic financial risk - Stefano Giglio (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
This paper measures the joint default risk of financial institutions by exploiting information about counterparty risk in credit default swaps (CDS). A CDS contract written by a bank to insure against the default of another bank is exposed to the risk that both banks default. From CDS spreads we can then learn about the joint default risk of pairs of banks. From bond prices we can learn the individual default probabilities. Since knowing individual and pairwise probabilities is not sufficient to fully characterize multiple default risk, I derive the tightest bounds on the probability that many banks fail simultaneously.
Keywords: G21; E44; G28; 330; credit default swaps; counterparty risk; default risk; simultaneous failures